Magma accumulation and segregation during regional-scale folding : the Holland’s dome granite injection complex, Damara belt, Namibia. - Kruger, Tolene Mia (Stellenbosch : Stellenbosch University, 2016)
Thesis (MSc)--Stellenbosch University, 2016.